2019
DOI: 10.3390/nu11092036
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet, a Rich Source of Angiopreventive Compounds in Cancer

Abstract: Diet-based chemoprevention of cancer has emerged as an interesting approach to evade the disease or even target its early phases, reducing its incidence or slowing down tumor progression. In its basis in the essential role of angiogenesis for tumor growth and metastasis, angioprevention proposes the use of inhibitors of angiogenesis in cancer prevention. The anti-angiogenic potential exhibited by many natural compounds contained in many Mediterranean diet constituents makes this dietary pattern especially inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 173 publications
(189 reference statements)
0
26
0
1
Order By: Relevance
“…Progress of cancer depends on the activation of pathways leading to inflammation and angiogenesis [50][51][52]. Many phytochemicals exert anti-inflammatory and anti-angiogenic activities [53][54][55]. Most of these compounds, like flavonoids, furanocoumarins, chalcones, stilbenoids, anthraquinones, and alkaloids, are also potent and specific inhibitors of CYP1B1 activity [56,57].…”
Section: The Role Of Cyp1b1 In Cancer Chemoprevention and Therapymentioning
confidence: 99%
“…Progress of cancer depends on the activation of pathways leading to inflammation and angiogenesis [50][51][52]. Many phytochemicals exert anti-inflammatory and anti-angiogenic activities [53][54][55]. Most of these compounds, like flavonoids, furanocoumarins, chalcones, stilbenoids, anthraquinones, and alkaloids, are also potent and specific inhibitors of CYP1B1 activity [56,57].…”
Section: The Role Of Cyp1b1 In Cancer Chemoprevention and Therapymentioning
confidence: 99%
“…To date, numerous scientific studies have shown that the MD protects from cardiovascular diseases 54–59 and certain types of cancer, 60–63 increases longevity, enables healthy aging 64‐70 and improves mental health and quality of life. Immunity boosting by adherence to an MD lifestyle is also reported by several authors, 71,72 as well as the diet's positive effects on metabolic syndrome and obesity, 73–78 diabetes 56,79–81 and hypertension.…”
Section: Health Benefits Of Mediterranean Dietmentioning
confidence: 99%
“…The Mediterranean dietary pattern (MDP), which is characterised by a high intake of vegetables, fruits, legumes, non-refined cereals, nuts, olive oil, moderate intake of fish and dairy products and low intake of red meat, could prevent gastric cancer. Because these ingredients containing an abundance of antioxidants could reduce DNA damage, they could also reduce H. pylori infection (19) and inhibit the angiogenesis process of tumours (20) . The DII, however, could reflect the inflammatory effect caused by diet (21) , which was a key process in gastric cancer initiation and progression (22) .…”
mentioning
confidence: 99%